2022
DOI: 10.3390/cancers14030813
|View full text |Cite
|
Sign up to set email alerts
|

Gas Plasma Exposure of Glioblastoma Is Cytotoxic and Immunomodulatory in Patient-Derived GBM Tissue

Abstract: Glioblastoma multiforme (GBM) is the most common primary malignant adult brain tumor. Therapeutic options for glioblastoma are maximal surgical resection, chemotherapy, and radiotherapy. Therapy resistance and tumor recurrence demand, however, new strategies. Several experimental studies have suggested gas plasma technology, a partially ionized gas that generates a potent mixture of reactive oxygen species (ROS), as a future complement to the existing treatment arsenal. However, aspects such as immunomodulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
3
4
0
Order By: Relevance
“…Our study highlights the potential of CAP as a putative adjunct or combinational therapy in lowgrade glioma treatment to improve surgical outcomes by selectively targeting cancer cell death. It is in line with previous studies where they highlighted the effectiveness of CAP jet in promoting cell cycle arrest, apoptosis, and immunomodulation in tissue samples obtained from glioblastoma and basal cell carcinoma patients [54,55].…”
Section: Discussionsupporting
confidence: 92%
“…Our study highlights the potential of CAP as a putative adjunct or combinational therapy in lowgrade glioma treatment to improve surgical outcomes by selectively targeting cancer cell death. It is in line with previous studies where they highlighted the effectiveness of CAP jet in promoting cell cycle arrest, apoptosis, and immunomodulation in tissue samples obtained from glioblastoma and basal cell carcinoma patients [54,55].…”
Section: Discussionsupporting
confidence: 92%
“…Based on the calculated IC50 values, the optimal exposure times were 70.15 and 138 s at the 48-h post-treatment time point for direct and indirect helium CAPs, and 202 and 116 s at the 72-h post-treatment time point for direct and indirect argon CAPs, respectively. This confirms previous studies 5 , 34 , which revealed that the effect of CAP on cell death is influenced by the exposure time and the duration of cultivation after treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study also exhibit that plasma treatment can be used as an effective and efficient method to treat the GBM cancer 29 . Based on these preclinical studies, CAP has holds great promise for clinical applications in GBM treatment 5 , 10 , 27 , 30 34 . However, these studies are still in the preclinical phase, and determining the optimal dose and duration of CAP treatment is necessary for complete GBM cure.…”
Section: Introductionmentioning
confidence: 99%
“…Such hot devices are sometimes also called by names known in ‘cold’ plasma medicine, such as Neutral Argon Plasma or PlasmaJet (NCT02376231, NCT049004042, NCT01596985, NCT04355312). In turn, cold gas plasma treatment of patient-derived tumor tissues elicits apoptosis [ [194] , [195] , [196] ]. Some companies marketing these electrosurgical devices started a few years ago to promote cold modes of their equipment.…”
Section: Clinical Gas Plasma Cancer Treatmentmentioning
confidence: 99%
“…About the latter, ex vivo gas plasma treatment of primary tumor tissues has been found to change the secretion profiles markedly when compared to untreated controls if the tumor tissue was cultured for several hours post gas plasma exposure. This was found for all tumor types investigated, i.e., melanoma [ 194 ], cutaneous SCC [ 196 ], basal cell carcinoma (BCC) [ 196 ], glioblastoma [ 195 ], breast cancer [ 202 ], and urothelial (bladder) cancer [ 203 ]. Transcriptomic analysis of the latter also revealed that such changes are the consequence of changed signaling pathways induced by gas plasma treatment rather than merely reflecting the loss of, e.g., the number of viable cells that would participate in cytokine secretion and binding and/or uptake.…”
Section: Clinical Gas Plasma Cancer Treatmentmentioning
confidence: 99%